Why and how is Scrum being adapted in practice: A systematic review - Hron, Michal; Obwegeser, Nikolaus (The Journal of systems and software, 2022)
Scrum, recognized today as the most popular agile development methodology, has been used in a wide range of settings and for varying purposes, in- and outside of the traditional software development context. The use of Scrum in non-traditional settings and for different needs led to a considerable corpus of academic literature that investigates, presents, and discusses modifications to the original method, aimed to make it fit such novel forms of application. Based on a large-scale review of extant literature, this study systematically analyses why and how Scrum was reportedly modified in different instances and contributes with a synthesis that can serve as a basis for a more systematic approach to future research and practice. We explicate nine common modification objectives for change (e.g., attaining high performance, non-standard contexts, distributed development) mapped against seven generic modification strategies (e.g., method guidance, new procedures, or artifacts). Building on our extensive literature analysis we highlight research gaps and identify promising areas for future research. •Scrum is used in many contexts but overview of its adaptations is missing.•Based on a review of 925 papers, we map why and how Scrum is modified.•We relate modification objectives (why) against modification strategies (how).•The literature lacks cumulative practice, hindering systematic research.•We analyze empirical validity and methodological variety to find research gaps.